2004
DOI: 10.7863/jum.2004.23.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Lung Volume Estimated by 3‐Dimensional Ultrasonography and Magnetic Resonance Imaging in Cases With Isolated Congenital Diaphragmatic Hernia

Abstract: There is a good agreement between 3-dimensional ultrasonography and magnetic resonance imaging for fetal lung volume estimation in cases with congenital diaphragmatic hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
2
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 19 publications
3
73
2
1
Order By: Relevance
“…Ipsilateral fetal lung volumes were measured by the same technique previously described in the literature [19][20][21][22][23] , using a Voluson 730 ultrasound machine (Kretztechnik, General-Electric, Zipf, Austria) with a 4-to 8-MHz transducer for three-dimensional volume scanning. A transverse section of the fetal thorax at the level of the four chamber view, with the fetal heart proximal to the transducer, was identified by 2DUS and the volume box was adjusted in order to scan the entire fetal thorax.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ipsilateral fetal lung volumes were measured by the same technique previously described in the literature [19][20][21][22][23] , using a Voluson 730 ultrasound machine (Kretztechnik, General-Electric, Zipf, Austria) with a 4-to 8-MHz transducer for three-dimensional volume scanning. A transverse section of the fetal thorax at the level of the four chamber view, with the fetal heart proximal to the transducer, was identified by 2DUS and the volume box was adjusted in order to scan the entire fetal thorax.…”
Section: Methodsmentioning
confidence: 99%
“…Total and contralateral fetal lung volumes can be measured precisely on 3DUS [23,24] correlating significantly with neonatal deaths [21,24] . Total fetal lung can be calculated using the rotational technique (VOCAL TM ) by summing the right and left lung volumes [19][20][21][22][23] . Initial results showed that an observed/expected total fetal lung volume ratio (o/e-TotFLVR) lower than 0.35 was significantly associated with neonatal deaths [21] , confirming the results of previous studies using MRI [15][16][17][18] .…”
mentioning
confidence: 99%
“…1,7 Nevertheless, in spite of the great advances in prenatal and postnatal diagnosis and management, the mortality rate in neonates with isolated CDH is still high. 8 Recent research has focused on prenatal predictors of neonatal outcome in isolated CDH cases, such as lung/head ratio 9,10 and fetal lung volume, [11][12][13][14][15][16] to differentiate cases with a worse prognosis, in which fetal therapy or termination of pregnancy may be indicated, from those with better prognosis, requiring only specialized postnatal care. [17][18][19] In spite of the worldwide, published experience, there are no data about perinatal results in cases of prenatally diagnosed CDH in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…fetuses with extremely reduced lung volumes, liver herniation and decreased pulmonary vascularization [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Neonatal deaths among severe CDH cases occur due to severe pulmonary hypoplasia and pulmonary arterial hypertension [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 99%